Kreativitas Produksi Video Konten sebagai Media Promosi Kegiatan Kampus - M Derry Amanda (INDO PUBLISHING, 2026)
This study aims to analyze the creativity involved in producing video content as a promotional medium for campus activities. The research is based on data obtained from an Independent Study/Project program conducted at BTV Universitas Bina Darma. This study uses a qualitative descriptive method through observation, documentation, and content analysis of campus promotional videos published on social media platforms. The results show that creative video production covering concept development, visual composition, editing techniques, and platform suitability plays an important role in increasing audience engagement and the effectiveness of campus activity promotion. Creative video content contributes not only to information dissemination but also to strengthening campus branding in the digital era..